Tick‐borne relapsing fever as a potential veterinary medical problem - Nusirat Elelu (Veterinary Medicine and Science, 2018)
Abstract Tick‐borne relapsing fever (TBRF) caused by the bacteria Borrelia, is poorly documented in veterinary medicine. Given the widespread presence of the soft tick vectors – Ornithodoros and the recently discovered hard tick vectors, as well as their close association with animal hosts, it is highly likely that infection occurs, but is rarely reported to be of veterinary importance. Sporadic reports of canine infection, some being fatal through to probable cause of abortion in horses have been published. Some of these pathogens exist in regions where there are limited diagnostic facilities, hence, they are likely to be missed and their impact on productivity may be unquantified. Here we review available literatures on cases of TBRF in domestic and wild animals in order to show their potential veterinary medical impact. Future efforts using field and laboratory surveys are needed to determine pathogenesis, vector competence and distribution in animals, their impact on animal health and productivity as well as to prevent further spill to the human population, where it is already a public health problem in some parts of the world.